ANALISIS KESALAHAN PENGGUNAAN TANDA BACA DALAM PENULISAN LAPORAN OBSERVASI STANDAR EBI SISWA KELAS VII SMP NEGERI 1 BAMBEL TAHUN 2021/2022 - Lisa Indah; Ati Rosmiati (STKIP USMAN SAFRI KUTACANE, 2022)
This research is a descriptive study that aims to describe the use of punctuation errors in writing EBI Standard Reports for Grade VII students. The approach used is a qualitative descriptive approach. The research was carried out at SMP Negeri 1 Bambel with the research subjects being 11th grade students. The data in this study are errors in the use of punctuation marks in writing EBI Standards for Class VII Students. The forms of errors in the use of punctuation were found, namely omission. The results of this study indicate that based on 11 student writings that have been analyzed, the biggest error in the use of punctuation marks is the omission of periods and commas between elements in a detail with an indication of inaccuracy and ignorance of students in the use of punctuation marks.